Training in Collecting, Appraising and Synthesising Evidence for EFSA scientific assessments. Issue 7 (6th July 2021) - de Vries, Rob; van Luijk, Judith; Hooijmans, Carlijn; Wever, Kim; Hoffmann, Sebastian; in 't Hout, Joanna; Langendam, Miranda; Tillema, Alice; Alkema, Wynand; Ritskes‐Hoitinga, Merel; ,
Abstract : The overall objective of project OC/EFSA/AMU/2018/01 was to support EFSA to develop in‐house capacity to collect, appraise and synthesize evidence coming from literature sources in the context of food and feed scientific assessment. This objective had to be reached by offering 3 different types of training courses to EFSA staff (including Trainees) and Experts (of Panels, Working Groups and Member States). This report summarizes these trainings and their evaluation. Between 15 October 2018 and 24 November 2020, 9 trainings were delivered by a team of trainers from SYRCLE (SYstematic Review Centre for Laboratory animal Experimentation, www.syrcle.nl ) and partners. A total number of 160 people participated in these trainings (an average of 18 per training), some of whom participated in more than one training (day). The individual trainings were evaluated using an online evaluation form, which consisted of general questions (e.g. about the training room or course material) and specific questions about the various parts of the training courses. The participants had the option of adding qualitative comments. Moreover, a so‐called second level evaluation was used to assess the extent to which the trainings improved the capacity of participants to use the techniques explained in the courses in the context of EFSA assessments. With an average score of 8.23 (out of 10), the trainings were evaluated very positively. Major revisions of the content were only necessary for two of the courses and only after the first editions. Overall, the participants assessed their knowledge and practical skills to be higher after the training compared to before. Moreover, two of the online editions of the courses received an EFSA Golden Globe for the most successful EFSA scientific courses delivered in 2020. Based on the experiences with this series of trainings, recommendations are made for future EFSA trainings in evidence synthesis.